Raychem RPG Ltd : strategic transformation - Karna, Amit; Garg, Amit (London : Indian Institute of Management, Ahmedabad, 2019)
The case describes the strategic transformation at Raychem RPG Ltd (RRL) - a joint venture between RPG group, India and TE Connectivity, USA. The case focuses on the various initiatives by Ramani Kasi, President and a long time employee of RRL.
Originally Published InKarna, A., & Garg, A. (2019). Raychem RPG Ltd: Strategic Transformation. IIMA/BP0424. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Raychem Corporation -- Case studies; Chemical industry -- Case studies; Business planning -- Case studies